Barter, Centralized Merchants and Geographical Spread - Noguera-Santaella, J (2011)
This essay analyses the circumstances under which a redistributive barter system with centralized merchants dominates over primitive unstructured barter. It emphasizes the role of the geographical spread to explain the emergence of structured trade. The model analytically shows how, in the presence of taste for variety and increasing returns to scale in the production of commodities, the opportunity cost of direct bartering interacts with the transport costs and the geographical spread to explain the existence of intermediaries, and provides some interesting links between the literature on market emergence and the birth and growth of cities. © 2010 the author(s). Journal compilation © 2010 RSAI.